Supraclavicular oblique incision sternocleidomastoid intermuscular approach versus traditional low collar incision linea Alba Cervicalis Approach in thyroid lobectomy (LATERAL study): the protocol for a multicenter prospective non-randomized controlled study - Cheng Qu; Yanbo Sun; Yanxue Wang; Bo Jiang; Chaoyu Jiang; Chen Zhang; Yue Wang; Jingchen Wang; Hua Xi; Yongzhao Chen; Dengyuan Yang; Yuqian Luo; et al. (BMC Surgery)
Abstract Background A Chinese multicenter prospective cohort study of supraclavicular oblique incision sternocleidomastoid intermuscular approach (SOI-SMIA) versus traditional low collar incision linea alba cervicalis approach (TCLI-LACA) in thyroid lobectomy for papillary thyroid carcinoma (LATERAL study) has been initiated. The aim is to compare surgical approach-related outcomes in thyroid lobectomy. We here outline the detailed protocol for this study. Methods PTC which can be treated by lobectomy is considered for inclusion in the study. Eligible patients will receive printed materials that detail the advantages and disadvantages of each management option, allowing them to select their preferred intervention. Thyroid lobectomy by SOI-SMIA or TCLI-LACA will be performed within 24 h after grouping. We designed a composite index of surgical approach-related trauma as the primary endpoint. It includes both the superficial (scar consciousness and appearance satisfaction) component and the deep component (neck impairment), and will be assessed at 1 month and 6 months after surgery. The LATERAL study will be conducted in three hospitals in China. We plan to recruit 80 patients per group and enroll patients consecutively over time and will conclude once the group with the smaller number of participants reaches 80 cases. Conclusion The results of this trial will contribute to confirming the role of SOI-SMIA in thyroid lobectomy for PTC, and provide evidence to support its wider adoption.